Are research ethics guidelines culturally competent?. (January 2017) - Gray, Ben; Hilder, Jo; Macdonald, Lindsay; Tester, Rachel; Dowell, Anthony; Stubbe, Maria
Research ethics guidelines grew out of several infamous episodes where research subjects were exploited. There is significant international synchronization of guidelines. However, indigenous groups in New Zealand, Canada and Australia have criticized these guidelines as being inadequate for research involving indigenous people and have developed guidelines from their own cultural perspectives. Whilst traditional research ethics guidelines place a lot of emphasis on informed consent, these indigenous guidelines put much greater emphasis on interdependence and trust. This article argues that traditional guidelines are premised on relationships of equal power, and that often the researcher has more power that is not fully equalized by providing information. Where there is a relationship of unequal power, then focusing on interdependence and trust is more likely to achieve ethical safety. We illustrate this thesis by describing the detail of a research project looking at the use of interpreters, where we video-recorded live consultations and then interviewed the patient, interpreter and doctor. We conclude by suggesting that mainstream research ethics guidelines should pay more attention to the development of a trustworthy relationship between subject and researcher, and that, following the lead from clinical medicine, we should develop a culturally competent ethical framework for research on human subjects.